Adjacent relations of primary phase fields and invariant reactions of the system CaO‐SiO2‐Nb2O5‐La2O3. Issue 5 (10th January 2021) - Liu, Chengjun; Qiu, Jiyu; Liu, Zhengyue; Zhu, Deying; Wang, Yeguang; Jiang, Maofa
Abstract: The adjacent relation of primary phase fields and corresponding invariant reactions of the system CaO‐SiO2 ‐Nb2 O5 ‐La2 O3 are of great importance for the study on its phase diagram. In the present work, the phase equilibrium in the high w (La2 O3 ) region of CaO‐SiO2 ‐Nb2 O5 ‐La2 O3 system was studied by thermodynamic equilibrium experiment. The adjacent relation of primary phase fields was determined and represented in the form of adjacent tetrahedrons. The Alkemade Rule applicable to quaternary phase diagram was deduced, which can be used to infer the liquidus temperature trend on univariant curves. The rule was then used to determine the possible temperature range of invariant reactions corresponding to the adjacent tetrahedron in CaO‐SiO2 ‐Nb2 O5 ‐La2 O3 system, and the result was shown in the form of Schairer diagram. Finally, the reaction types of five invariant points were determined according to the Lever Rule for quaternary phase diagram, including: ① L1 +CaO·3SiO2 ·2La2 O3 →CaO·SiO2 +SiO2 +La2 O3 ·Nb2 O5, ② L2 →CaO·SiO2 +La2 O3 ·Nb2 O5 +SiO2 +CaO·Nb2 O5, ③ L3 +CaO·3SiO2 ·2La2 O3 +2CaO·Nb2 O5 →10CaO·6SiO2 ·Nb2 O5 +La2 O3 ·Nb2 O5, ④ L4 +10CaO·6SiO2 ·Nb2 O5 →CaO·SiO2 +2CaO·Nb2 O5 +La2 O3 ·Nb2 O5, ⑤ L5 +2CaO·Nb2 O5 →CaO·Nb2 O5 +La2 O3 ·Nb2 O5 +CaO·SiO2 . Abstract : Adjacent tetrahedrons and corresponding invariant points of the CaO‐SiO2 ‐Nb2 O5 ‐La2 O3 system.